Community-Based sustainable tourism on commonages : an alternative to traditional land reform in Namaqualand, Northern Cape Province - Wilson, G.D.H. (University of Pretoria, 2013)
Thesis (PhD (Tourism Management))--University of Pretoria, 2007.